Analysis of Government Agency Leadership : How does The Effect on Employee Discipline? - Yones, Novita; Khumayah, Siti; Rahmayanti, Rahmayanti (ann4publisher@gmail.com, 2025)
Employee discipline refers to attitudes and behaviors that are in accordance with the rules, policies, and procedures that have been established by the organization. Research This discusses the analysis of leadership in agency government And How it affects disciplined employees. Purpose study: To identify the effect of discipline on employees as a consequence of the implementation of leadership by agency government. Theory Adair about role leadership And Rivai Veitzhal discipline employee become knife analysis research conducted at the Cangkuang Village Office, Babakan District, Cirebon Regency. Research This approach is qualitative with design studies case. Locus research at Cangkuang Village Office, Babakan District, Cirebon Regency with take research data through observation, study documentation, And method interviews with the Head of Village Office, Secretary of Village Office, and Employee of Cangkuang Village, Babakan District, Cirebon Regency. Research results show that leadership in agency government is run by the Head Village through the planning, initiating, controlling, supporting, informing, and evaluating indicators. However, in its implementation, violations of disciplined employees in the form of unexpected arrivals​ at appropriate times were still found, and the fulfillment performance of the employee was hampered because online services sometimes​​ find constraints at the level center. Based on the condition above, there is function supervision for the leader who has not walked in the Village Office coconut shell Cirebon Regency, and the indicators are Not listed in the theory used in the research. However, in reality, they play a role in the enforcement of discipline, as do employees at the Village Office Cangkuang Cirebon Regency.